Effect of D-Allethrin Aerosol and Coil to the Mortality of Mosquitoes - Sayono Sayono; Puji Lestari Mudawamah; Wulandari Meikawati; Didik Sumanto (Tehran University of Medical Sciences, 2019)
Background: Commercial insecticides were widely used by communities to control the mosquito population in their houses. D-allethrin is one of insecticide ingredients widely distributed in two different concentrations namely 0.15% of aerosol and 0.3% of coil formulations. We aimed to understand the mortality of indoor mosquitoes after being exposed to d-allethrin 0.15% (aerosol) and 0.3% (coil) formulations. Methods: This quasi-experiment study applied the posttest-only comparison group design. The aerosol and coil d-allethrin were used to expose the wild mosquitoes in twelve dormitory bedrooms of SMKN Jawa Tengah, a vocational high school belonging to Central Java Provincial Government, on March 2017. The compounds were exposed for 60 min to each bedroom with four-week interval for both of formulations. The knockdown mosquitoes were collected into a plastic cup and delivered to the laboratory for 24h holding, morphologically species identification and mortality recording. History of insecticide use in the dormitory was recorded by an interview with one student in each bedroom. Data were statistically analyzed with independent sample t-test and Mann-Whitney. Results: As many as 57 knockdown mosquitoes belonging to three species were obtained namely Culex fuscocephala, Cx. quinquefasciatus and Aedes aegypti with mortality rate of 50.88% after 24h holding. Knockdown and mortality of mosquitoes were significantly different based on d-allethrin formulations. D-allethrin concentrations were not effective for controlling Culex mosquitoes but effective for Ae. aegypti. Conclusion: Further efficacy of d-allethrin 0.15% aerosol to eradicate Ae. aegypti is necessary to be conducted in supporting the Dengue vector control.